2019
DOI: 10.1111/eje.12459
|View full text |Cite
|
Sign up to set email alerts
|

Depression, anxiety and stress in a cohort of Australian dentistry students

Abstract: Introduction Dentistry students face a challenging academic and clinical curriculum that can result in depression and anxiety. While studies usually report sources of stress for dentistry students, there is less information on levels of stress. This study used the Depression, Anxiety and Stress Scale (DASS‐21), to report perceived levels of depression, anxiety and stress in a cohort of Australian undergraduate dentistry students. Methods Students enrolled in years 1‐4 of the Bachelor of Dental Science (Honours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
63
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 33 publications
7
63
0
7
Order By: Relevance
“…We found that 35.5% (95% CI [29.1-42.2%]), 33.2% (95% CI [27-39.9%]) and 24.9% (95% CI [19.3-31.2%]) of the undergraduate medical students, including resident interns showed symptoms of depression, anxiety, and stress respectively during COVID-19 outbreak with the majority with moderate depression (15.2%), moderate anxiety (17.5%), and mild stress (13.4%). Based on the severity ranking, subjects with moderate and above ranking may present with a possible problem that may require intervention (Crawford & Henry, 2003;Lovibond & Lovibond, 1995;Page, Hooke & Morrison, 2007;Stormon et al, 2019). In this study, 23.9%, 26.7% and 11.5% of the study population presented with moderate to extremely severe levels of depression, anxiety, and stress respectively (Fig.…”
Section: Discussionmentioning
confidence: 68%
“…We found that 35.5% (95% CI [29.1-42.2%]), 33.2% (95% CI [27-39.9%]) and 24.9% (95% CI [19.3-31.2%]) of the undergraduate medical students, including resident interns showed symptoms of depression, anxiety, and stress respectively during COVID-19 outbreak with the majority with moderate depression (15.2%), moderate anxiety (17.5%), and mild stress (13.4%). Based on the severity ranking, subjects with moderate and above ranking may present with a possible problem that may require intervention (Crawford & Henry, 2003;Lovibond & Lovibond, 1995;Page, Hooke & Morrison, 2007;Stormon et al, 2019). In this study, 23.9%, 26.7% and 11.5% of the study population presented with moderate to extremely severe levels of depression, anxiety, and stress respectively (Fig.…”
Section: Discussionmentioning
confidence: 68%
“…Fifty‐eight studies were included, and Figure 1 shows the flowchart for the studies selection process. Fifteen different instruments were used to assess self‐reported depressive symptom in the included studies: Beck Depression Inventory (BDI), 25–43 Depression Anxiety Stress Scale (DASS), 44–61 Hospital Anxiety and Depression Scale (HADS), 62–66 Zung Depressive Scale, 67–69 Goldberg Anxiety and Depression Scale, 70 Hamilton Depression Rating Scale (HDRS), 71 Kutcher Adolescent Depression Scale, 72 Patient Health Questionnaire (PHQ)‐2 73 , PHQ‐9 74–76 , Aga Khan University Anxiety and Depression Scale, 77 Center for Epidemiological Studies‐Depression, 78 General Health Questionnaire‐28, 79 Mental Health Inventory, 80 Hopkins Symptom Checklist, 81 Symptom Questionnaire 82 . Table S1 summarizes the main characteristics of all tools used in the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Only 9 of the included studies were cohort, 38,39,44,54,63,66,69,74,82 and follow‐up ranged from 2 months 63 to 4 years 82 . Overall, 16,805 dental students were involved in the present systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…A growing body of literature suggests that health care graduate students, including pharmacy, medical, and dental students, experience psychological distress, including anxiety, depression, or perceived stress, at significantly higher rates than their age-matched peers. [1][2][3] Burnout, a workplace syndrome characterized by exhaustion, reduced empathy, and diminished sense of accomplishment, may develop concurrently with anxiety and depression. 4 Burnout in students is associated with increased anxiety, depression, suicidal ideation, substance use, thoughts of dropping out of school, and poorer school performance.…”
Section: Introductionmentioning
confidence: 99%